2012
DOI: 10.1371/journal.pone.0051544
|View full text |Cite
|
Sign up to set email alerts
|

ROS Production Is Essential for the Apoptotic Function of E2F1 in Pheochromocytoma and Neuroblastoma Cell Lines

Abstract: In this study we demonstrate that accumulation of reactive oxygen species (ROS) is essential for E2F1 mediated apoptosis in ER-E2F1 PC12 pheochromocytoma, and SH-SY5Y and SK-N-JD neuroblastoma stable cell lines. In these cells, the ER-E2F1 fusion protein is expressed in the cytosol; the addition of 4-hydroxytamoxifen (OHT) induces its translocation to the nucleus and activation of E2F1target genes. Previously we demonstrated that, in ER-E2F1 PC12 cells, OHT treatment induced apoptosis through activation of cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…This is consistent with numerous observations indicating that ROS generation is a critical event regulating E2F1-dependent apoptosis (52)(53)(54), and mitochondrial stress response pathway activates E2F1 in an ROS-dependent manner (55).…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with numerous observations indicating that ROS generation is a critical event regulating E2F1-dependent apoptosis (52)(53)(54), and mitochondrial stress response pathway activates E2F1 in an ROS-dependent manner (55).…”
Section: Discussionsupporting
confidence: 93%
“…Currently, there is no SDHB -mutated PHEO/PGL cell line available; therefore, we used N2a cells, which are derived from mouse neuroblastoma. Neuroblastoma-derived cells are frequently used in studies of PHEO/PGL as neuroblastoma is a tumor of neural crest origin that shares numerous similarities with PHEO/PGL [31, 32]. A viability assay was performed on N2a cells with silenced Sdhb (si Sdhb -N2a) to model tumors lacking functional SDHB, similar to SDHB -related PHEO/PGL (Supplementary Figure S1F, S1G).…”
Section: Resultsmentioning
confidence: 99%
“…We considered the E2F1 transcription factor as a potential candidate to establish a link between pVHL activity and OMA because pVHL is a direct downstream target of E2F1 [63]. In addition, recently it was reported that the phosphorylated and active form of E2F1 is regulated in ROS-dependent manner [64], [65]. ROS-dependent phosphorylation of E2F1 has previously been investigated in some detail.…”
Section: Resultsmentioning
confidence: 99%
“…ROS-dependent phosphorylation of E2F1 has previously been investigated in some detail. ATM protein kinase is phosphorylated by cellular ROS to act as a redox sensor in cells, and ROS-dependent phosphorylation of ATM activates the effector kinase Chk2, which in turn phosphorylates its downstream target, E2F1 [32], [64], [66], [67].…”
Section: Resultsmentioning
confidence: 99%